2019
DOI: 10.15694/mep.2019.000181.1
|View full text |Cite
|
Sign up to set email alerts
|

Depression Among Medical Students of Karachi A Cross Sectional Study

Abstract: Introduction: Depression is a mood disorder characterized by loss of interest in daily activity, feeling of hopelessness and helplessness, decreased appetite, anger and irritability. The risk factors which leads to depression include academic demands, daily habits, sleeping hours, sedentary lifestyle, inability to cope, helplessness, increased psychological pressure, mental tension and increased work load etc. The objective of current study is to find out the prevalence of depression among students of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…As far as the genderwise difference of depression is concerned, a few studies from Pakistan have reported a high frequency of depression among female students compared to males. 11,12,20 This statement agrees with the present study, as the frequency of females (50.5%) was high, even with a significantly higher (16%) percentage of female medical students with mild depression as compared to male students (figure 3). In contrast to the present study, Mubashir et al has reported no gender difference in developing depression symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As far as the genderwise difference of depression is concerned, a few studies from Pakistan have reported a high frequency of depression among female students compared to males. 11,12,20 This statement agrees with the present study, as the frequency of females (50.5%) was high, even with a significantly higher (16%) percentage of female medical students with mild depression as compared to male students (figure 3). In contrast to the present study, Mubashir et al has reported no gender difference in developing depression symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…Of them, 2/3 of the participants were married females, while 3/4 th participants were single. 11 Another cross-sectional study with undergraduate medical students from private and public medical colleges in Karachi reported a 9.7% prevalence of depression, being more common in female students (9.6%) than males (7.3%). 12 A survey of medical students in Faisalabad, Punjab revealed 57.1% depression.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that depression was higher among students' who were not satisfied with their lives, were socially isolated, had trouble sleeping, little control over things and future depends on others. Studies have identified the prevalence of depression in association with lifestyle habits, sleeping hours, physical activities, recent trauma, and coping mechanisms in Pakistan's medical students (Alvi et al, 2010;Jadoon et al, 2010;Kumari et al, 2019).…”
Section: Discussionmentioning
confidence: 99%